One-Liners - N. M. Martinez-Rossi; C. Andrade-Monteiro; S. R.C. Pombeiro; M. Orbach; H. Liu; T. J. Schmidhauser; P. A. Hubbard; C. H. Wilson (Fungal Genetics Reports, 1992)
One liners from: N.M. Martinez-Rossi, C. Andrade-Monteiro and S.R.C. Pombeiro; M. Orbach ; H. Liu and TJ. Schmidhauser; P.A. Hubbard and C.H. Wilson